Challenges of Implementing Public Involvement in Environmental Approval in the Regions - Nida Alifah Amir; Wiwin Widiyaningsih; Yeni Nuraeni; Yuki Rahmat Fauzi (Unifikasi: Jurnal Ilmu Hukum, 2026)
This study aims to analyze the implementation of public involvement in environmental approvals under Article 26 of Law Number 32 of 2009 in Majalengka Regency, addressing the gap between legal norms and field reality. Purpose: The purpose is to identify the implementation, assess its effectiveness, and examine the factors inhibiting public participation. Methods: In order to achieve the stated objectives, a socio-legal method was adopted, with descriptive-analytical qualitative analysis. Data were collected through in-depth interviews with 20 respondents, comprising 10 affected community members and 10 academics, alongside literature reviews. Results: The obtained results showed that public participation remains an administrative formality, as the community reported being ignored, subjected to intimidation, and burdened by complicated bureaucratic processes, while academics pointed to weaknesses in regulations and local government capacity. Conclusion: Based on the observations, it was inferred that public involvement was ineffective, primarily because the factor remained confined to procedural formalities. Suggestion: To address this issue, suggestions include comprehensive structural reforms, such as implementing environmental education, strengthening the apparatus capacity, and integrating digital technology to facilitate access to information and minimize conflict. Contribution: The contribution and novelty of this study are in the integration of a procedural justice framework into the evaluation of environmental approvals through a triangulation of perspectives. By repositioning public participation as a governance instrument that determines legitimacy and accountability, the present investigation produces implementation indicators replicable enough to support more inclusive policy improvements in the future.